Utilization of part C early intervention services for patients with cleft palate. (December 2021) - Kay, Hannah G.; Lipscomb, Brittany; Zhao, Shilin; Shannon, Chevis; Phillips, James D.
Abstract: Objectives: To investigate the utilization of early intervention services under Part C of the 2004 Individuals with Disabilities Educational Act for children with cleft palate and to better understand barriers these patients encounter when receiving services. Methods: A retrospective chart review was performed on children under the age of 18 who were treated for cleft palate at a single tertiary care center and referred to Tennessee's Early Intervention System (TEIS) between January 2007 and December 2018. Results: For the 61 patients included, developmental therapy was the most common TEIS referral made (n = 408, 28%), followed by speech therapy (n = 371, 26%). Most of these services were delivered as scheduled (n = 513, 80%); some families missed appointments without notifying the provider (i.e., family no-show)(n = 101, 2%). Children referred at a younger age were more likely to receive developmental therapy (p = 0.012) and to attend their services (p = 0.027). Patients with Medicaid were more likely to have absences with prior notification (p = 0.05) and without prior notification (i.e., family no-show)(p = 0.009) than patients with other types of health insurance. Conclusions: Patients with cleft palate often have complex needs; earlier referral to ancillary services may improve attendance at appointments and impact the services they receive. Socioeconomic factors may hinder patients from accessing these services even once they are referred.